SELECTION OF TACTICS IN SURGICAL TREATMENT OF LIVER ECHINOCOCCOSIS - Khakimov, M.Sh.; Botirov, D.Y (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To improve the results of treatment of liver echinococcosis by improving surgical tactics using miniinvasive technologies. Materials and Methods: From 2013 to 2018, in the surgical department of the Urgench regional multidisciplinary medical center, 257 patients with liver echinococcosis were hospitalized. Surgical interventions were performed in 235 patients. Patients with combined echinococcosis of the liver and lungs were operated on in two stages. Digital material processed by the method of variation statistics. Results: Surgical treatment of residual echinococcosis of the liver differs from the primary treatment in greater trauma, postoperative complications were noted in 11.4%. This is due to the predominance of inflammatory and dystrophic changes in the fibrous membrane in residual echinococcosis, which require an increase in the volume of pericystectomy, as well as a predominance of extrahepatic abdominal cysts. Total pericystectomy significantly increased intraoperative blood loss in both primary and residual echinococcosis of the liver. During the early postoperative period, a sign of early postoperative intestinal obstruction was observed in 2% of patients, with repeated surgery, diffuse bleeding was detected. In 6 patients, external bile leakage was noted through the drainage tubes of the residual cavity. Suppuration of postoperative wounds was observed in 2 patients. Lethal outcomes were registered in 1.7% of cases. Recurrence of the disease was 7.7%. Conclusion: Radical surgical treatment of primary and residual liver echinococcosis allows in most cases to achieve good results. For uncomplicated cysts without daughter blisters, puncture-drainage methods are effective. The use of these treatments for centrally located cysts needs evaluation